PENGARUH DUKUNGAN ORGANISASI TERHADAP KOMITMEN SATGAS PPKS DALAM PENANGANAN DAN PENCEGAHAN KEKERASAN SEKSUAL DILINGKUNGAN UNIVERSITAS - Syatriawan Perdana Putra; Isti Dari Sofianti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
Sexual violence in higher education institutions is a serious issue that requires special attention. To address this problem, universities have established Task Forces for the Prevention and Handling of Sexual Violence (SATGAS PPKS) as part of their efforts to create a safe campus environment. This study aims to analyze the influence of organizational support on the commitment of SATGAS PPKS in carrying out their duties of preventing and handling sexual violence. Organizational support is defined as the perception of SATGAS members regarding the attention, appreciation, and resources provided by the organization, while organizational commitment includes affective, continuance, and normative aspects. This research adopts a quantitative approach with a survey method. Data were collected through questionnaires completed by active SATGAS PPKS members from various universities, with a population of 200 individuals and a sample of 67 individuals determined using Slovin's formula. Instrument validity and reliability tests were conducted, while simple regression analysis was employed to test the influence of the independent variable on the dependent variable with the help of the SPSS software. The results indicate that organizational support has a significant influence on the commitment of SATGAS PPKS. This finding suggests that a positive perception of organizational support can enhance the emotional, moral, and sustainable engagement of SATGAS PPKS members in performing their duties. This research implies that universities need to strengthen organizational support through appreciation for members' contributions, the provision of adequate facilities, and attention to their welfare. Optimal support will contribute to a high level of commitment among SATGAS members in creating a campus environment free from sexual violence